1982
DOI: 10.21273/jashs.107.2.248
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Temperature on Flowering of Alstroemeria ‘Regina’1

Abstract: When Alstroemeria ‘Regina’ plants were programmed to flower after 6 or 8 weeks at 5°C treatments, flowering was hastened by forcing plants at 18° vs. 13° greenhouse night air temperature. However, the 18° forcing temperature reduced flower production, flowers per shoot and shoot grade when compared to 13° forcing temperatures. Due to the decrease in flower production observed at 18° forcing temperature, a 13° temperature is recommended. When plants were grown for 16 weeks at 13°, an inductive temperature, or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Even though we have been able to induce flowering in March by the use of HID lighting, we are unable to promote rapid flowering in early winter, or shortly after the completion of the cold treatment in December (5,6 ).…”
Section: Methodsmentioning
confidence: 74%
“…Even though we have been able to induce flowering in March by the use of HID lighting, we are unable to promote rapid flowering in early winter, or shortly after the completion of the cold treatment in December (5,6 ).…”
Section: Methodsmentioning
confidence: 74%
“…Although researchers have investigated the effect of alternating temperatures (10,15), constant low air temperatures (4,5,7,13,14,15), or high air temperatures (4,5,8,13,14) on growth and flowering of alstroemeria, no one yet has shown a definite relationship between controlled soil temperature and floral induction (Table 1) or soil/air temperature X photoperiod with flower induction and generative shoot production of Alstroemeria 'Regina' (Table 2). Lin (11) reported that circulating 10°C tap water in pipes 25 cm below the soil surface increased spring-summer production, and a 16-hr high-pressure sodium lighting regime reduced flowering.…”
Section: Soil Temperaturementioning
confidence: 99%
“…The exact control mechanisms for Alstroemeria 'Regina' flower induction, initiation, and development are not clearly understood (4,5,6,7,8). Several workers have shown the influence of air temperature on generative alstroemeria shoot induction and subsequent shoot and flower development (3,5,6,7,9,10,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In winter, only plants treated with the combination of soil cooling and HPS lighting produced flowers.Recent research on Alstroemeria (Lily-ofthe-Incas) flowering has been devoted to its earliness (3, 4). Early flowering increases the production span and thereby productivity, because all Alstroemeria plants cease flow ering at about the same time, regardless of previous photoperiod treatments (5).Temperature and light have been studied previously with regard to Alstroemeria flow ering (1,3,4,9). It has been suggested that Alstroemeria flowering involves a phasic mechanism in which thermophase precedes photophase (3).…”
mentioning
confidence: 99%